Hygienic Analysis Of Morbidity Indicators Of Patients: On The Example Of The Endocrine System - Nizom, Ermatov J.; Ikhtiyor, Abdulkhakov U.; Khosiyat, Sadullaeva A.; Mamlakat, Rustamova T.; Sanam, Khayrullaeva S.; Rano, Dadaboyeva K.; Akromjon, Saliyev R. (International Journal of Membrane Science and Technology, 2023)
In this article, the quantitative and qualitative indicators of the hygienic analysis of protein, fat, oil, carbohydrates, vitamins and minerals in the daily diet of patients with endocrine system diseases in the Bukhara region of our country, the role of protein, fat, oil, carbohydrates, vitamins and minerals in the diet and its importance in disease prevention is assessed and practical recommendations are given to prevent unhealthy nutrition and hypodynamia during the development of the disease.